Định hướng thiết kế chương trình đào tạo nghề cho thanh niên các dân tộc ít người vùng Tây Nguyên và Đông Nam Bộ - Do, Mạnh Cường (Journal of Technical Education Science, 2007)
Curriculum development and choosing of teaching methods are always started from the learners analysis because educational objects are always specific individuals of different types. There is no corporate curriculum nor an optimal teaching method for all types of learners. Based on the research outcomes on vocational learning characteristics of the ethnic minority youth in Highlands and Southeast area of Vietnam, we see that it is nec- essary to choose a way of curriculum development and choosing of teaching methods in order to meet those characteristics. In our opinion, Competencies-Based Traning (CBT) approach shoud be considered